2018
DOI: 10.1183/16000617.0104-2017
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vascular development in congenital diaphragmatic hernia

Abstract: Congenital diaphragmatic hernia (CDH) is a rare congenital anomaly characterised by a diaphragmatic defect, persistent pulmonary hypertension (PH) and lung hypoplasia. The relative contribution of these three elements can vary considerably in individual patients. Most affected children suffer primarily from the associated PH, for which the therapeutic modalities are limited and frequently not evidence based. The vascular defects associated with PH, which is characterised by increased muscularisation of arterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 62 publications
1
31
1
Order By: Relevance
“…Previous studies indicated that abnormal pulmonary vascular development and function is a significant clinical problem in CDH infants 29 . In our cohort, CDH cases with LD variants had higher PH prevalence at 1 or 3 months compared to cases without LD variants.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies indicated that abnormal pulmonary vascular development and function is a significant clinical problem in CDH infants 29 . In our cohort, CDH cases with LD variants had higher PH prevalence at 1 or 3 months compared to cases without LD variants.…”
Section: Discussionmentioning
confidence: 98%
“…Alternatively, poor gas exchange may suggest persistently impaired perfusion of fifth and sixth generation pulmonary vessels that are important for gas exchange. In CDH, reduced pulmonary vascular cross-sectional area in combination with extensive hypermuscularisation and neomuscularisation of distal pulmonary vessels is thought to lead to higher resistance within peripheral pulmonary vessels 35. Luks et al suggested that short-term tracheal occlusion (2 weeks) reduces abnormal muscularisation of pulmonary arterioles; however, their histological analysis defined distal vessels by size, rather than branching generation 36.…”
Section: Discussionmentioning
confidence: 99%
“…Lung development occurs in four stages starting at 4 weeks’ gestation and continuing into the postnatal period 2627. Lung budding is seen from 16 to 24 weeks’ gestation, and alveolar formation and maturation from 24 weeks’ gestation to 3 years of postnatal life 26.…”
Section: Fetal Endoscopic Surgeriesmentioning
confidence: 99%
“…Lung budding is seen from 16 to 24 weeks’ gestation, and alveolar formation and maturation from 24 weeks’ gestation to 3 years of postnatal life 26. Concurrent with this process is pulmonary vascular development which occurs through neovascularization and branching of pre-existing conduits between weeks 10 and 11 27282930. Initially the pulmonary vessels are thick and muscular with high vascular resistance that decreases with gestation and after birth to promote gas exchange 27.…”
Section: Fetal Endoscopic Surgeriesmentioning
confidence: 99%
See 1 more Smart Citation